Strategi Dinas Kesehatan Provinsi Jawa Tengah dalam Mengatasi Stunting - Amalia Mulyani; Fauzan Hidayatullah; Hasya Rahmah; Sugih Sugiharta; Ricardo Cordias; Noer Apptika Fujilestari (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Stunting in children under five is a critical health problem that affects physical and cognitive development as well as potential future productivity. In Indonesia, the prevalence of stunting is still high, especially in Central Java. This research explores the Central Java Health Service's strategy in overcoming stunting through a qualitative approach using library research. This research shows the results that the Central Java Health Service has formulated policies in accordance with the RPJMN and the direction of the Ministry of Health, focusing on improving health status at all stages of life. Flagship programs such as "Centing Apik" in Kebumen and "Centing Emas" in Magelang aim to improve the possibilities and quality of health and nutritional infrastructure for mothers and children. Even though the reduction in stunting rates is not yet significant, the Health Service's commitment to accelerating the reduction in stunting prevalence is carried out through program optimization, cross-sector collaboration, and public education about nutrition and healthy lifestyles. This strategy includes five stages: goals, environment, direction, action, and measurement. This research concludes that sustainable and integrated efforts are needed to significantly reduce the prevalence of stunting in Central Java.